Transformasi Ekosistem Non-Tunai Berbasis Qris Sebagai Strategi Peningkatan Daya Saing UMKM di Era 5.0 - Desta Dinda Lestary; Normanda Domeyro Latief; Ida Ayu Nuh Kartini (As-Syirkah: Islamic Economic & Financial Journal, 2026)
The current digital era 5.0 has led to a shift in people's transaction patterns, shifting from cash to non-cash payments. This situation presents an opportunity for MSMEs to utilize digital payments as a strategy to increase competitiveness and sales. This article was written to analyze the transaction strategy used by Warung Sate Bu Murkam to increase sales through the implementation of a digital payment system using non-cash payments. The method used is a descriptive approach by examining the implementation of digital payments and their impact on service and increasing business sales. The results of the discussion indicate that the use of non-cash payments, such as QRIS, can provide convenience in transactions, speed up the payment process, increase customer convenience, and help make financial records more effective and accurate. Although there are obstacles such as dependence on internet networks and unequal understanding of digital payments among customers, the benefits obtained outweigh the challenges faced. Thus, the implementation of digital payments is an effective strategy for Warung Sate Bu Murkam in boosting sales and strengthening business competitiveness in the digital era 5.0.